Advances in coastal structures and breakwaters proceedings of the international conference organized by the Institution of Civil Engineers and held in London on 27-29 April 1995 - Clifford, J. E. (Thomas Telford, 1996)
These conference proceedings present authoritative papers on new experience and research, particularly that which has led to advances in design procedures. It covers design, construction and performance experience of coastal structures and breakwaters particularly including new developments.